2021
DOI: 10.1038/s41598-021-88856-7
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive in-planta acclimation responses to basal growth and acute heat stress were induced in Arabidopsis by cattle manure biochar

Abstract: In-planta mechanisms of biochar (BC)-mediated improved growth were evaluated by examining oxidative stress, metabolic, and hormonal changes of Arabidopsis wild-type plants under basal or acute heat stress (–HS/ + HS) conditions with or without BC (+ BC/–BC). The oxidative stress was evaluated by using Arabidopsis expressing redox-sensitive green fluorescent protein in the plastids (pla-roGFP2). Fresh biomass and inflorescence height were greater in + BC(‒HS) plants than in the –BC(‒HS) plants, despite similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 101 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…Although POD activity increased by 70% when treated with S. constrictum under drought stress, SOD activity nearly doubled under HTs with the same inoculant compared with control. In addition, Kumar et al [127] observed biochar effects under HTs in Arabidopsis. Results revealed that, under HTs (50 • C), lipid peroxidation significantly increased compared with control samples.…”
Section: High Temperaturementioning
confidence: 99%
“…Although POD activity increased by 70% when treated with S. constrictum under drought stress, SOD activity nearly doubled under HTs with the same inoculant compared with control. In addition, Kumar et al [127] observed biochar effects under HTs in Arabidopsis. Results revealed that, under HTs (50 • C), lipid peroxidation significantly increased compared with control samples.…”
Section: High Temperaturementioning
confidence: 99%
“…The roGFP2 reporter is particularly promising because, unlike HyPer, it is not sensitive to pH. Heat stress was shown to increase oxidation in chloroplasts using roGFP2 as a redox sensor ( Kumar et al., 2021 ). Because roGFP2 does not readily react with H 2 O 2 , yeast GPX Orp1 was fused to roGFP2 to enhance its specificity for H 2 O 2 ( Gutscher et al., 2009 ).…”
Section: Resultsmentioning
confidence: 99%